The Growth Returns of Health: Investments, Outcomes, And Cointegrated Development in Türkiye (Third Sector Social Economic Review, 2025)
This study examines the long-run relationship between health capital and economic growth in Türkiye from 2000 to 2023.  We apply both Fully Modified Ordinary Least Squares (FMOLS) and Canonical Cointegrating Regression (CCR) methods to analyze how health indicators stem from government health expenditures, life expectancy, and infant mortality, interact with traditional growth determinants composed of physical capital, labor force, and human capital to influence GDP. The results reveal three key findings: First, health investments yield substantial economic returns, with 1% increases in health spending and life expectancy associated with 0.10% and 0.14–0.19% GDP growth, respectively. Second, infant mortality reductions show particularly strong growth effects, confirming the economic urgency of child health interventions. Third, conventional factors remain pivotal, with capital accumulation (0.23 elasticity) and labor expansion (0.57–0.62 elasticity) driving growth alongside human capital improvements. These findings underscore the necessity of integrated policymaking that synergizes health, education, and economic strategies. We recommend prioritizing: (1) cost-effective health expenditures with dual productivity benefits, (2) equitable healthcare access to address regional disparities, and (3) human capital development to amplify health-growth linkages. The study provides empirical support for viewing health investments as fundamental drivers of sustainable development rather than mere social expenditures.
Keywords: Economic Growth; Health Expenditures; Life Expectancy; Infant Mortality; Cointegration Regressions